The impacts of COVID-19 on children in Australia: deepening poverty and inequality. Issue 4 (4th July 2022) - Bessell, Sharon
ABSTRACT: Australia's response to COVID-19 has been effective in limiting transmission, resulting in fewer cases than in many countries. Nevertheless, the pandemic and responses to it have created serious social and economic problems that are impacting negatively on children. Existing inequalities have been exacerbated, poverty is deepening, and relationships are under pressure, with highly deleterious consequences for children. Despite the significant impacts on children, they have been largely invisible in policy responses and there have been no serious attempts on the part of political leaders to engage with children or respond to their concerns. This viewpoint draws on research undertaken prior to the pandemic with children aged between seven and twelve years to analyse the ways in which COVID-19 responses are likely to impact on children.